Cryoprotectant Influence on Fluorescence of Potato Meristems - Lysak, Yu. S.; Stribul, T. F.; Kompaniets, A. M. (Problems of Cryobiology and Cryomedicine, 2011)
We have investigated the dependence of potato meristems fluorescence on effect of the agents with cryoprotective properties on meristems. Meristems treated with cryoprotectant were irradiated with laser, fluorescence was excited and in 1, 3, 5, 120 min the fluorescence spectra were recorded. We have found that the effect of cryoprotective agents was manifested in the fluorescence intensity change within investigated wave length range.